A proteomic‐based investigation of potential copper‐responsive biomarkers: Proteins, conceptual networks, and metabolic pathways featuring Penicillium janthinellum from a heavy metal‐polluted ecological niche. Issue 4 (9th May 2017) - Feng, Xin; Xu, Jian; Liang, Yu; Chen, Guo‐Li; Fan, Xian‐Wei; Li, You‐Zhi
Abstract: Filamentous fungi‐copper (Cu) interactions are very important in the formation of natural ecosystems and the bioremediation of heavy metal pollution. However, important issues at the proteome level remain unclear. We compared six proteomes from Cu‐resistant wild‐type (WT) Penicillium janthinellum strain GXCR and a Cu‐sensitive mutant (EC‐6) under 0, 0.5, and 3 mmol/L Cu treatments using iTRAQ. A total of 495 known proteins were identified, and the following conclusions were drawn from the results: Cu tolerance depends on ATP generation and supply, which is relevant to glycolysis pathway activity; oxidative phosphorylation, the TCA cycle, gluconeogenesis, fatty acid synthesis, and metabolism are also affected by Cu; high Cu sensitivity is primarily due to an ATP energy deficit; among ATP generation pathways, Cu‐sensitive and Cu‐insensitive metabolic steps exist; gluconeogenesis pathway is crucial to the survival of fungi in Cu‐containing and sugar‐scarce environments; fungi change their proteomes via two routes (from ATP, ATP‐dependent RNA helicases (ADRHs), and ribosome biogenesis to proteasomes and from ATP, ADRHs to spliceosomes and/or stress‐adapted RNA degradosomes) to cope with changes in Cu concentrations; and unique routes exist through which fungi respond to high environmental Cu. Further, a general diagram of Cu‐responsive paths and a model theory of high Cu are proposed at the proteome level. Our work not only provides the potential protein biomarkers that indicate Cu pollution and targets metabolic steps for engineering Cu‐tolerant fungi during bioremediation but also presents clues for further insight into the heavy metal tolerance mechanisms of other eukaryotes. Abstract : Our work not only provides the potential protein biomarkers indicating the Cu pollution, target metabolic steps for engineering the Cu‐tolerant fungi during bioremediation, but also presents clues for insight into heavy metal tolerance mechanisms of other eukaryotes.